Perception of clinical supervisors on occupational therapy undergraduates' clinical fieldwork in Malaysia - Dzalani Harun; Tan, Eileen; Hanif Farhan Mohd Rasdi (Penerbit Universiti Kebangsaan Malaysia, 2024)
Clinical fieldwork is an important component in an occupational therapy program for undergraduates to obtain clinical skills and experience. Feedback from clinical supervisors is valuable as it helps to develop a better clinical fieldwork system. In Malaysia, there is a lack of well-documented feedback from clinical supervisors, particularly in the occupational therapy field. Thus, this study aimed to examine and compare the perception of clinical supervisors toward clinical fieldwork based on areas of practice and grades of post and to determine its association with the clinical supervisors’ duration of clinical experience in Malaysia. A quantitative cross-sectional study design was adopted. Data was collected using the Clinical Supervisors’ Perception Survey Questionnaire (CSPSQ). Ninety-five occupational therapists across 12 government hospitals participated as respondents to the questionnaire. The total mean score of the CSPSQ showed that clinical supervisors' perception of the current clinical fieldwork system was positive overall. No significant differences were observed between domain scores among the practice areas and a post's grades (p>0.05). There was also no significant association between the duration of clinical experience and the domain scores (p> 0.05). In conclusion, clinical supervisors generally have a positive perception of the current clinical fieldwork system regardless of area of practice, grade of post or duration of clinical experience, indicating that the clinical fieldwork system for occupational therapy undergraduate students is relevant to the current context.